CHALLENGES FACED BY ENGLISH TEACHERS IN TEACHING VOCABULARY TO RURAL JUNIOR HIGH SCHOOL STUDENTS IN BALI: Tantangan Yang Dihadapi Guru Bahasa Inggris Dalam Mengajarkan Kosa Kata Kepada Siswa SMP Perdesaan di Bali - I Gusti Ngurah Octova Seventilofa (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Vocabulary mastery is a fundamental component of English language proficiency and plays a crucial role in developing students’ listening, speaking, reading, and writing skills. However, teaching vocabulary in rural EFL contexts presents unique challenges, particularly in regions with limited educational resources. This study aims to explore the challenges faced by English teachers in teaching vocabulary to rural junior high school students in North Bali, Indonesia. Employing a qualitative case study approach, data were collected through in-depth interviews, classroom observations, and document analysis involving English teachers from rural junior high schools. The findings reveal that teachers encounter multiple interrelated challenges, including limited instructional resources, students’ low exposure to English, inadequate vocabulary learning strategies, and contextual constraints related to rural educational settings. These challenges significantly affect the effectiveness of vocabulary instruction. The study contributes to EFL pedagogy by providing context-specific insights and pedagogical implications for improving vocabulary teaching in rural secondary education